2018
DOI: 10.1111/ddg.13529
|View full text |Cite
|
Sign up to set email alerts
|

Vertical transmission of herpes simplex virus: an update

Abstract: Herpes simplex virus (HSV)-1 and -2 infections are highly prevalent worldwide. HSV infection during pregnancy can result in neonatal herpes infection, which is characterized by lifelong infection with periods of latency and reactivation. HSV can be acquired by an infant during one of three periods: in utero (5 %), peripartum (85 %), or postnatal (10 %). Neonatal HSV is a rare but significant infection that may be associated with severe morbidity and mortality, especially if there is dissemination or central ne… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
26
1
6

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 23 publications
(33 citation statements)
references
References 42 publications
0
26
1
6
Order By: Relevance
“…Vertical transmission is the passage of a pathogen from mother to child that can occur still in the uterus (hematogenous transplacental), peripartum or during the postnatal period. 23 In the present study, the prevalence of HSV-1 DNA found in placenta samples was 37.5% (n ¼ 60), which is considered high when compared with other studies that also identified the occurrence of HSV only in the placenta and reported prevalence rates between 2.6 and 28%. [14][15][16][17][18] These findings demonstrate that the virus prevalence in placental tissue is frequent among the pregnant women who joined the study.…”
Section: Discussioncontrasting
confidence: 54%
See 1 more Smart Citation
“…Vertical transmission is the passage of a pathogen from mother to child that can occur still in the uterus (hematogenous transplacental), peripartum or during the postnatal period. 23 In the present study, the prevalence of HSV-1 DNA found in placenta samples was 37.5% (n ¼ 60), which is considered high when compared with other studies that also identified the occurrence of HSV only in the placenta and reported prevalence rates between 2.6 and 28%. [14][15][16][17][18] These findings demonstrate that the virus prevalence in placental tissue is frequent among the pregnant women who joined the study.…”
Section: Discussioncontrasting
confidence: 54%
“…10,11,18 The presence of the virus in the blood nourishing the fetus during pregnancy is facilitated by its occurrence in the placenta, which is a tissue shown to be permissive to HSV infection in vitro. 23,26 There are few studies investigating HSV vertical transmission using the cord blood as a target tissue. Finger-Jardim et al 19 studied the prevalence of HSV-2 in the placenta, and found viral DNA in 9% of the analyzed tissues and a 1.1% incidence in the umbilical cord blood of newborns.…”
Section: Discussionmentioning
confidence: 99%
“…Although a significant number of people are already infected with HSV, epidemiological studies in maternal HSV transmission indicate that pre-existing immunity may reduce the number of newly transmitted infections and associated pathological consequences. Specifically, the rate of viral transmission in pregnant mothers is higher for primary than recurrent infection [12]. Furthermore, primary infections in the third trimester of pregnancy have a higher transmission rate compared to the first trimester [13,14], probably due to the shorter span of time for establishment of anti-viral immune responses.…”
Section: Introductionmentioning
confidence: 99%
“…A number of clinically relevant viruses can be vertically transmitted from mothers to their foetus, including Zika virus, HIV, hepatitis B virus, hepatitis C virus, HSV-1 and -2, varicella zoster virus, Rubella virus, parvovirus B19 and CMV, and can cause stillbirth or severe morbidity in infants [88][89][90][91][92][93][94]. In the context of preterm birth (PTB) and small-for-gestational age (SGA) births, biological mechanisms are still poorly understood.…”
Section: Adverse Birth Outcomesmentioning
confidence: 99%